Private tutoring and the question of equitable opportunities in Turkey - Aysıt Tansel (Turkish Economic Association, 2013)
This paper focuses on the implications of private tutoring in Turkey for questions of equity regarding the provision of public education, based on an analysis of previously published research. The nature of the private tutoring and its relation to the two national selection examinations in Turkey are also discussed.
Keywords: I21; I24; I25; 330; Turkey; private tutoring; educational equity; national selection examinations; Privatschule; Bildungschancen; Türkei